Transformation toward sustainability in Finnish teacher education policy: Promises and shortcomings - Wolff, Lili-Ann; Laherto, Antti; Cheah, Saiki; Vivitsou, Marianna; Autio, Minna (Frontiers in Education, 2022)
While the state of the world is becoming ever more unsustainable, transformation and transformative learning have become increasingly relevant and raised attention in various sustainability education discourses. This is obvious in both policy and research. As teacher educators, we have studied how this sustainability and transformative education trend is visible in education policy. We have first read international policy and research on sustainability education and transformation. In a more thorough study, our focus has been on two recent and fundamental policy documents outlining the Finnish teacher education. Our results show that even if several UNESCO policies documents for years have called for a transformation towards sustainability through education, the Finnish teacher education policy has not yet fully acknowledged sustainability issues and teachers’ transformative agency in addressing them, but emphasize other aims. Therefore, it is mainly up to the individual teacher educators and the leaders of their faculties to decide on how to prepare students teachers not only to deal with changes in general, but to particularly bring about changes towards sustainability.